Factor analysis in optimization of formulation of high content uniformity tablets containing low dose active substance - Lukášová, Ivana; Muselík, Jan; Franc, Aleš; Goněc, Roman; Mika, Filip; Vetchý, David (European journal of pharmaceutical sciences, 2017)
Warfarin is intensively discussed drug with narrow therapeutic range. There have been cases of bleeding attributed to varying content or altered quality of the active substance. Factor analysis is useful for finding suitable technological parameters leading to high content uniformity of tablets containing low amount of active substance. The composition of tabletting blend and technological procedure were set with respect to factor analysis of previously published results. The correctness of set parameters was checked by manufacturing and evaluation of tablets containing 1-10mg of warfarin sodium. The robustness of suggested technology was checked by using "worst case scenario" and statistical evaluation of European Pharmacopoeia (EP) content uniformity limits with respect to Bergum division and process capability index (Cpk). To evaluate the quality of active substance and tablets, dissolution method was developed (water; EP apparatus II; 25rpm), allowing for statistical comparison of dissolution profiles. Obtained results prove the suitability of factor analysis to optimize the composition with respect to batches manufactured previously and thus the use of metaanalysis under industrial conditions is feasible.
Keywords: Common blend; Factor Analysis, Statistical; Factor analysis; Drug Liberation; Tablets; příprava léků; Worst case; tablety; faktorová analýza statistická; warfarin; Process optimization; uvolňování léčiv; Sampling error; Dissolution method; Content uniformity; Drug Compounding; antikoagulancia; Anticoagulants; Warfarin